Discovery of Laacher See eruption in speleothem record synchronizes Greenland and central European Late Glacial climate change - Warken, Sophie F.; Schmitt, Axel Karl; Scholz, Denis; Hertwig, Andreas; Weber, Michael; Mertz-Kraus, Regina; Reinig, Frederick; Esper, Jan; Sigl, Michael (Science advances, 2025)
To assess the impact of ongoing, historically unprecedented Arctic ice melting, precisely synchronized chronologies are indispensable for past analogs of abrupt climate change. Around 12,900 years before present (B.P.), the Atlantic-European realm experienced an abrupt relapse to near-glacial climate conditions attributed to Arctic meltwater fluxes, the Younger Dryas. However, it remained unclear how fast this climatic change propagated southward into Europe as terrestrial and ice-core chronologies are not sufficiently synchronized. Here, we use a volcanic sulfur spike identified in a speleothem from Germany to link the Laacher See eruption (LSE), a key chronostratigraphic marker in European terrestrial archives, to a previously unidentified sulfate spike in the Greenland ice-core record. The LSE, dated to 13,008 ± 8 years B.P.1950, thus synchronizes radiometric and ice-core calendars back in time, which consistently demonstrates that the LSE predates the onset of the Younger Dryas cooling by about 150 years, both in Greenland and Europe.